DYNAMICS OF CYTOKINES IN ORAL FLUID OF COMPLETELY EDENTULOUS PATIENTS AFTER PROSTHETIC REHABILITATION WITH IMPLANTS - V.A. Ponomarenko; Y.I. Sylenko; M.V. Khrebor (Ukrainian Medical Stomatological Academy, 2016)
One of the most difficult tasks in modern prosthetic dentistry is total rehabilitation of patients with dentition defects. The number of patients with removable dentures is growing due to the widespread dental diseases and progressive aging of the world population especially in industrialized countries, where life is increasing. After a complete loss of teeth, dentition undergoes involute processes, resulting in significant functional and morphological changes. In practice of rehabilitation of toothless jaws certain difficulty of fixation of dentures on the lower jaw appears. As a result, patients rest unsatisfied with the received dentures. The introduction of dental implantation in prosthodontics practice offers the prospect of successful treatment of patients with the manufacture of fixed and conditionally removable dentures. Generally accepted that the combination of modified immunological background before dental implantation and operational stress create conditions for the appearance of secondary immunological suppression, which can be the cause of serious inflammatory and destructive processes in the long-termed period. Basing on the current states of Clinical Immunology, it can be assumed that the cytokine profile of the blood is essential for the overall characteristics immunological pathogenesis of the most chronic diseases, including dental ones. Particularly, current studies have prowed the importance of cytokines and intercellular interactions in the pathogenesis of chronic generalized periodontitis. Proved that elevated level of pro-inflammatory cytokines IL-1β, TNF is seen as a key component of any resorptive and inflammation process in the soft and bone structures. The objective is to study the concentration of proinflammatory cytokines (FNPα, IL-1β) and anti-inflammatory cytokines (IL-10) in the oral fluid of completely edentulous patients after rehabilitation on implants in different periods of observation. Materials and methods: Under our supervision there were 23 completely edentulous patients requiring rehabilitation on implants after one-step mandible protocol. The age of patients is between 67 and 78 years, including 11 males (46.7%) and 12 - females (53.3%). The control group consisted of almost healthy persons - 10 people without defects of dentition and periodontal diseases, aged 45-55 years. The patients of both groups (the basic and the control one) were examined comprehensively using the following methods: clinical, paraclinical, immunological and radiological. Dental status was assessed after finding out of complaints, medical history, review of maxillofacial area with the following objective assessment of teeth and dentition, temporomandibular joint. The research of patients of the control group consisted of determining the status of implants and evaluation of marginal gum mucosa, periimplantal area, the degree of compliance and mobility of soft tissues. Methods of the research of periimplantal area, bone structures, alveolar processes became panoramic radiography and computed tomography. Content in oral fluid FNPα, IL-1 β and IL-10 was evaluated by the method of ELISA, using Pro Con (NPO "Protein circuit" G. Saint - Petersburg). Results: Increased level of TNF, IL-1β and IL-10 before prosthetic rehabilitation relates to dates of prosthetic rehabilitation of the patients of 2 groups. Thought prosthetic rehabilitations were performed on average of 2 weeks after implantation surgery. The high level of cytokines 7 days after the imposition of the prosthesis relates to the restruction of bone tissue and oral mucosa because of the development of adaptation to new conditions of mastication associated with prosthetic treatment. Received data indicates the lack of immunological regulation mechanisms in the tissues of the oral cavity at the stages of adaptation to prosthetic constructions. It was found that patients before treatment and especially 7 days after prosthesis have maximum values of concentrations of proinflammatory and anti-inflammatory cytokines in oral fluid on the contrary to healthy people. This data confirms that the activation of local synthesis of proinflammatory cytokines in oral fluid is an important pathogenic factor that determines the formation and maintenance of active inflammatory reaction in the gingival tissue and initiates resorptive process in the alveolar bone.